Sequential injection spectrophotometric system for evaluation of mushroom tyrosinase-inhibitory activity - Nuntaporn Moonrungsee (2018)
A sequential injection (SI) spectrophotometric method with absorbance detection at 475 nm has been developed for evaluating activity of some compounds on an inhibition of the mushroom tyrosinase. The method involved a reaction of 3,4-dihydroxyphenylalanine (l-DOPA) and mushroom tyrosinase to form the o-dopaquinone. The decrease of the o-dopaquinone was related to an increase of tyrosinase-inhibitory activity. Under the optimum conditions (concentration and volume of l-DOPA and mushroom tyrosinase of 2.0 mM, 60 μL and 142 U mL-1, 15 μL, respectively), some antioxidant compounds were examined for the tyrosinase-inhibitory activity. A batch enzymatic assay of tyrosinase-inhibitory activity was applied as the reference method for comparison. The results of IC50values obtained from the proposed method and the batch method were correlated well, with r2of 0.969. The SIA provides higher precision and degrees of automation, consumes smaller amounts of chemicals and it is simpler and faster than the batch method. © 2012 Elsevier B.V. All rights reserved.